2013
DOI: 10.1155/2013/684930
|View full text |Cite
|
Sign up to set email alerts
|

Sonodynamic Excitation of Rose Bengal for Eradication of Gram-Positive and Gram-Negative Bacteria

Abstract: Photodynamic antimicrobial chemotherapy based on photosensitizers activated by illumination is limited by poor penetration of visible light through skin and tissues. In order to overcome this problem, Rose Bengal was excited in the dark by 28 kHz ultrasound and was applied for inactivation of bacteria. It is demonstrated, for the first time, that the sonodynamic technique is effective for eradication of Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli. The net sonodynamic effect was calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 47 publications
(53 reference statements)
3
74
0
Order By: Relevance
“…Although we used higher fluences and lower MB concentrations, our findings are in good agreement with those of previous studies, as shown in Table 3 (Yow et al, 2011; Huang et al, 2012; Nakonechny et al, 2013; Vecchio et al, 2015). …”
Section: Discussionsupporting
confidence: 93%
“…Although we used higher fluences and lower MB concentrations, our findings are in good agreement with those of previous studies, as shown in Table 3 (Yow et al, 2011; Huang et al, 2012; Nakonechny et al, 2013; Vecchio et al, 2015). …”
Section: Discussionsupporting
confidence: 93%
“…51 Following on from their previous studies on the photodynamic inactivation of microorganisms exploiting the chemiluminescent oxidation of luminol as the light source, 52 the authors focus on the ultrasound radiation as the initiator of dye-sensitised cell damage. When E. coli cells were incubated with rose Bengal (0-15 µM, 15 min) and subsequently exposed to ultrasound irradiation in the dark (to avoid the photodynamic activation of the sensitiser) a reduction of up to 3-log in the bacterial population was observed (initial load: 10 9 CFU/mL).…”
Section: Sact Mediated By Photosensitisersmentioning
confidence: 99%
“…undertook the second major study into the antimicrobial potential of SACT and investigated the susceptibility of both E. coli and the Gram‐positive organism, Staphylococcus aureus to the modality. This study utilised an established SS, Rose Bengal (RB), which eradicated high levels of both organisms and appeared to be activated by sonoluminescence (Nakonechny et al ., ), which are light flashes induced in biological media by acoustic cavitation events (Rooze et al ., ). In combination, the results of these SACT investigations are in line with the emerging view that this modality generally involves the direct electronic excitation of SS via a photochemical pathway similar to that involved in PACT.…”
Section: Sonodynamic Antimicrobial Chemotherapymentioning
confidence: 99%
“…The activation of these SS by light and ultrasound leads to a toxicity to target cancer cells that is greater than that of either SDT or PDT alone and includes effects such as enhanced ROS production (McCaughan et al ., ) and the promotion of SS uptake via the ultrasound‐mediated enhancement of cell membrane permeability (Wang et al ., , b; Li et al ., ). No SS involved in SPDT has yet been tested for its antimicrobial activity although RB possesses antibacterial activity based on both SACT (Nakonechny et al ., ) and PACT (Rossoni et al ., ) and produces higher levels of ROS when activated by sound and light in combination as compared to either radiation alone (McCaughan et al ., ).…”
Section: Sonophotodynamic Antimicrobial Chemotherapy?mentioning
confidence: 99%
See 1 more Smart Citation